APLIKASI PANDUAN DAN MONITORING PADA IBU HAMIL BERBASIS ANDROID GUIDANCE AND MONITORING APLICATION OF ANDROID BASED PREGNANT WOMEN - Agusalim Syamsudin Pure; Uning Lestari; Erma Susanti (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2018)
Pregnancy is a process kodratih experienced by all the women, Felt the new man growing in his stomach. With the condition of them know about what is new is the important thing so that the birth would go well. This study aims to make application to ease pregnant women obtain information pregnancy, monitoring the development of and run activity mother during pregnancy by using based program android. The materials used in this research are the results of the interviews with the midwife who are competent, Pregnancy books and journals online about pregnancy. The methodology used is the literature study and observation. The guidelines and monitoring aplication of pregnant women was built use of language java, fire, mysql database, web servers apache and ideas android studio. The application of a guide and monitoring pregnant women this constructed in the form of the android application. This application using one actor namely users. Users can only run application made .The application of the guidelines and monitoring pregnant women was built to provide information to user every week pregnancy, Monitor statisitk the development of weight and a reminder to help run user activity. The result obtained was that the application of help user obtain information pregnancy in the form of articles every week da other information. The development of the statistics and a reminder agenda to help user .